MANAJEMEN DAN ETIKA PENGELOLAAN ZAKAT MENURUT TINJAUAN SYARIAH - SUKARNI, SUKARNI (Universitas Islam Negeri Antasari Banjarmasin, 2013)
One of the pillars of Islam establishment is implementation of Zakat encashment. Zakatbecome one of the five pillars of Islam which one and others work in synergy. How important zakatis, Allah refers to people who are not fulfilled it as religion liars (Surah al-Ma'un). The importance ofthe Zakat can be seen from the mission of Islamic sharia as the teaching that committed toimplement physical and spiritual welfare, spiritual material. Zakat become instruments tend to thewelfare of the people. In Indonesia, it has entered the consciousness of the state. This was evidencedby the publication of two laws on zakat, Law No. 38 of 1999 and Law No. 23 of 2011 on Zakat. Thispaper explores the management of zakat as a part of the responsibility of the state, in addition tomanagement and ethical management.